The effect of warm compress intervention on post herniotomy pain - Ika Cahyaningsih; Wenny Savitri; R. Anggono Joko Prasojo (Proceedings Series on Health & Medical Sciences, 2020)
The most complaint symptom for post herniotomy patients is pain on the surgical site. Pain may affect patients' ability to mobilize and may attribute to prolonged length of stay in the hospital. Many complementary therapies have been used to decrease pain intensity for patients post-surgery, but warm compress intervention on post herniotomy pain has not been explored significantly. To investigate the effect of warm compress intervention on post herniotomy pain. The study used a pre-post test quasi-experimental with control group design. Sixteen post herniotomy adult patients of Wates Kulon Progo District General Hospital of Yogyakarta were recruited for each group. The intervention group was given warm compress interventions two times per day for two days. Pain intensity was assessed pre and post-intervention with the Numerical Rating Scale, while the control group only received regular analgetic. The researchers used the Wilcoxon Signed-Rank Test and Mann-Whitney U Test to compare pain intensity in each group and between groups.Fifteen out of 16 patients who received warm compress intervention rated decreased pain intensity as the rest did not experience any differences after the intervention (Z=-3.354, p=.001). Unlike the control group, only 3 out of 16 patients experienced declined pain intensity after two days of herniotomy when the rest did not encounter any changes (Z=-1.732, p=.083). The mean rank between intervention and control groups were significantly different (U=20.000, p=.000). Warm compress intervention is a non-invasive nursing intervention which is effective in reducing the pain intensity of post herniotomy patients.